Madonna in Adoration - Stone, George Eathl (photographer):::Creator::::::::::::
Photograph of an Italian sculpture of the Madonna in Adoration, inset in an alcove. The scene is overseen by two cherubs; at the crest, a crown is held in hands, extending from above, by Andrea della Robbia (1435-1525).